Gestão da procura de energia numa rede de distribuição inteligente incluindo energias renováveis - Bernardo José Malhado Ferreira da Silva (2018)
With merging various smart facilities and equipment like intelligent electric devices, advanced metering infrastructures as well as Internet of Things (IoT) into different sections of power systems especially distribution section, consideration of demand response programs is going to be much easier in order to ensure the secure, economic and less emission pollutant operation of smart grids. High penetration of renewable energy sources such as photovoltaic systems and wind generators in large scale, as power plants or small scale as individual producers, lead to lots of variation in power production. Customers play an active role in modern electric network as small-scale producers. In other words, in addition to renewable sources of customer, their potential for participation in demand-side management makes them key elements of the network. Likewise, some smart appliances, smart monitoring, electric vehicle and potential of smart management in houses enable them to be much stronger and more reliable for all kinds of demand response programs. However this capabilities and abilities should be managed and organized to take the whole their advantage.